Quests for healing and identity in the fiction and films of John Sayles : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Albany, New Zealand - Peacock, Clare Elizabeth (Massey University, 2001)
John Sayles, writer and independent filmmaker, is, first and foremost a storyteller. The "stories" in his fiction and films tell of individuals trying to come to terms with personal and/or political issues and often lead their protagonists on journeys or quests in search of healing and identity. These quests frequently involve characters returning to places either from the past, or to the source of the trauma in order to understand and deal with the present. This thesis examines this particular aspect of the fiction and films of John Sayles.
Keywords: United States; Motion picture producers and directors; Sayles, John, 1950- -- Criticism and interpretation